Association between Self-perceptions of Periodontal Health and Electronic Cigarette use in Young Adults - Miguras, Maite (2023)
Background: The present study aimed to determine the association between self-perceptions of periodontal health and electronic cigarette use. Material and Methods: The study used an observational, analytical and cross-sectional design. 189 young adults aged 18 to 29 from the Metropolitan area of Lima, Peru, were recruited. In order to evaluate self-reported periodontal health, a questionnaire conceived by Quiroz et al. (2017) was used. This includes 13 questions divided into two dimensions (habits and self-perceived periodontal health). Poisson regression with robust variance was used to examine associations between qualitative variables and calculate raw and adjusted prevalence ratios. Results: 59.46% of participants using electronic cigarettes were found to have a poor perception of gum health. Statistically significant associations were produced between poor perceptions of gum health and vaping, regarding both raw data (PR=0.81; 95% CI: 0.69-0.95; p=0.011) and data adjusted to consider covariates (PR=0.82; 95% CI: 0.69-0.97; p=0.021). No associations were observed for the dimensions of bleeding during brushing, reddish, and/or swollen gums. Conclusion: A relationship was found between poor perceptions of gum health and electronic cigarette use.